The Effect Of Personality Traits And Inclusive Leadership On Work Engagement: The Role Of Job Crafting As Mediation And Mindfulness As Moderation - Marwah Nuraeni; Minto Yuwono; Aceng Ulumudin (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of personality traits and inclusive leadership on work engagement in Generation Z with job crafting as a mediating variable and mindfulness as a moderation variable. The study used a quantitative approach with a survey method of 205 Generation Z respondents who work in various companies in Indonesia. The sampling technique used purposive sampling and data analysis was carried out using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results of the study show that personality traits and inclusive leadership have a significant positive effect on job crafting, and job crafting has a significant positive effect on work engagement. In addition, job crafting has been proven to be able to mediate the influence of personality traits and inclusive leadership on work engagement. However, personality traits and inclusive leadership do not have a direct effect on work engagement, while mindfulness is not able to moderate the relationship between job crafting and work engagement. This study concludes that work engagement in Generation Z is more influenced by proactive behavior in shaping jobs through job crafting than internal psychological factors.